2014
DOI: 10.3748/wjg.v20.i26.8351
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic fatty liver disease and polycystic ovary syndrome

Abstract: Nonalcoholic fatty liver disease (NAFLD) is the most common cause of chronic liver disease in the Western world comprising a spectrum of liver damage from fatty liver infiltration to end-stage liver disease, in patients without significant alcohol consumption. Increased prevalence of NAFLD has been reported in patients with polycystic ovary syndrome (PCOS), one of the most common endocrinopathies in premenopausal women, which has been redefined as a reproductive and metabolic disorder after the recognition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
120
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(122 citation statements)
references
References 105 publications
0
120
0
2
Order By: Relevance
“…The liver is involved in lipid synthesis, transportation and storage, as well as in glucose and insulin metabolism (Paschos & Paletas 2009), all key factors in PCOS pathogenesis (den Boer et al 2004, Paschos & Paletas 2009, Baranova et al 2011, Vassilatou 2014. One of the most frequent hepatic affections, related to metabolic abnormalities, is nonalcoholic fatty liver disease (NAFLD), which affects 20-30% of the general population (Vassilatou 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The liver is involved in lipid synthesis, transportation and storage, as well as in glucose and insulin metabolism (Paschos & Paletas 2009), all key factors in PCOS pathogenesis (den Boer et al 2004, Paschos & Paletas 2009, Baranova et al 2011, Vassilatou 2014. One of the most frequent hepatic affections, related to metabolic abnormalities, is nonalcoholic fatty liver disease (NAFLD), which affects 20-30% of the general population (Vassilatou 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding premenopausal women, NAFLD has been mostly studied in patients with polycystic ovary syndrome (PCOS), and it has been shown that it is more prevalent in these patients (13). PCOS is characterised by hyperandrogenism and ovulatory dysfunction and is one of the most common endocrinopathies in premenopausal women, affecting 6-19% of this population depending on the used diagnostic criteria (14).…”
Section: Introductionmentioning
confidence: 99%
“…In clinical practice, obese women with PCOS may develop a chronic inflammatory hepatic condition, also known as non-alcoholic steatohepatitis (NASH), which may vary from 30 to 86% in many case studies. NASH reaches 100% occurrence in those case studies which use both ultrasound screening and laboratory exams as well [4]. The only presence of adipose liver, associated to enlarged waist measurement, identifies these women as phenotypically thin but metabolically fat, even in absence of increased BMI (Table 2).…”
Section: Traditional Physiopathological Characteristics (With Low Conmentioning
confidence: 99%